Colonic Tuberculosis Clinically Misdiagnosed as Anorexia Nervosa and Radiologically and Histopathologically as Crohn’s Disease - Tariq A Madani (Canadian Journal of Infectious Diseases)
A case of colonic tuberculosis presenting with severe wasting was misdiagnosed as anorexia nervosa at another institution. Double contrast barium enema showed strictures, and ulcerations of the cecum and ascending colon with a skip area. The radiologist believed that these findings were due to Crohn's disease. Colonoscopic biopsies from the involved area revealed histopathological changes typical of Crohn's disease and not tuberculosis. The patient completely recovered with antituberculous therapy without steroids. The case demonstrated the clinical, radiological and histopathological difficulties and misdiagnoses that may be associated with the diagnosis of colonic tuberculosis.